SOCIALIZATION ON HOW TO CHOOSE THE RIGHT COSMETICS FOR TEENAGERS - Aprilia Suryan Dini; Franssisca Dita Mayangsari; Eka Wulan Ndari; Putricia Citra Ardelia; Firnanda Mashlahatus Syintia (Journal of Community Research and Engagement, 2025)
Background: Cosmetics are one of the products with a large market share. The high demand for cosmetic products encourages some manufacturers to deliberately add harmful ingredients to their products to gain significant profits. Objectives: This community service aims to socialize how to choose the right cosmetics needs to be conducted as a provision for the community to avoid harmful cosmetic products, especially among teenagers who are easily deceived by advertisements on social media. Therefore, the community service team from the Bachelor of Pharmacy Program at Universitas Muhammadiyah Lamongan  conducted socialization on how to choose the right cosmetics for teenagers. Method: This activity was carried out at SMA Negeri 3 Lamongan (Class XII – 2) using counseling methods with PowerPoint media and banners. The success of this activity was analyzed through pre-test and post-test results. Results: The results showed that the average post-test score was higher than the pre-test score, indicating an increase in participants’ knowledge after the socialization activity. This activity is expected to have a positive impact on the community, especially the students of Class XII – 2 at SMA Negeri 3 Lamongan. Conclusion: This program has successfully increased in post-test scores compared to pre-test scores, meaning that the participants’ knowledge imporved after the socialization.